(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to determine the categories in the priority selection of religious tourism sites and determine the decision support model for determining religious tourism locations in Lampung Province. This study uses the AHP (Analytical Hierarchy Process) method with data processing using statistical calculations. The criteria in this study include reputation, site information, and site transactions. In this study, the criterion of tourists having visited the three religious tourism sites was involved, namely; Tomb of Sheikh Tubagus Yahya, Tomb of Raden Intan II, Tomb of Al Habib Ali Bin Alwi Al Idrus. The results of the study concluded that based on communal considerations (all criteria) the AHP method was sequential; Ayekh Tubagus Yahya Tomb (50.5%), Raden Intan II Tomb (30.9%), and Al Habib Ali bin Al Wialidrus Tomb (18.6%). Site Transactions from the three destinations get the lowest score of the three indicators. This shows that site transactions have not been a priority in selecting religious tourism destinations.